Исследование теплового состояния асинхронного частотно-управляемого двигателя с помощью метода конечных элементов - Осташевский, Н.А.; Шайда, B.П.; Петренко, А.Н. (Електротехніка і електромеханіка, 2011)
Research into thermal state of a frequency-controlled asynchronous motor with a finite element method is conducted. Results obtained are compared with results of the motor thermal state calculation by means of an equivalent thermal scheme method.